2021
DOI: 10.3390/ijms22095011
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to Establish Embryo-Derived Pluripotent Stem Cells in Cattle

Abstract: Stem cell research is essential not only for the research and treatment of human diseases, but also for the genetic preservation and improvement of animals. Since embryonic stem cells (ESCs) were established in mice, substantial efforts have been made to establish true ESCs in many species. Although various culture conditions were used to establish ESCs in cattle, the capturing of true bovine ESCs (bESCs) has not been achieved. In this review, the difficulty of establishing bESCs with various culture condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
(167 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Pillai et al [83] enhanced the cellular reprogramming of bovine fibroblasts to biPSCs by forcing expression of OCT4, SOX2, KLF4, and MYC, but they also reported that inhibition of ALK4/5/7 to block TGFβ/activin/nodal signaling together with GSK3β and MEK1/2 supported robust in vitro self-renewal of naive biPSCs. A detailed review of these topics was recently reported [89].…”
Section: Capturing Pluripotency In Vitromentioning
confidence: 99%
“…Similarly, Pillai et al [83] enhanced the cellular reprogramming of bovine fibroblasts to biPSCs by forcing expression of OCT4, SOX2, KLF4, and MYC, but they also reported that inhibition of ALK4/5/7 to block TGFβ/activin/nodal signaling together with GSK3β and MEK1/2 supported robust in vitro self-renewal of naive biPSCs. A detailed review of these topics was recently reported [89].…”
Section: Capturing Pluripotency In Vitromentioning
confidence: 99%